2020
DOI: 10.21873/invivo.11968
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study for 3D-printed Poly(methyl methacrylate)-resin Tracheostomy Tube Using a Hamster Cheek Pouch Model

Abstract: Background/Aim: A three-dimensional (3D) printed tracheostomy tube has potential application for patients who require a specialized tube. The aim of this study was to evaluate the characteristics of various 3D printing materials and determine their use in producing 3D-printed tracheostomy tube. Materials and Methods: Mechanical, chemical, and microbiological in vivo changes in the scaffolds were analyzed using a hamster cheek pouch (HCP) model. Results: The poly methyl methacylate (PMMA)-resin showed superior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Overall, the filler-loaded PMMA-based resin is considered suitable for use in dental applications, such as temporary crowns, provisional restorations, and denture bases. However, there is scope for further assessment of the cytotoxicity of PMMA-based reins to confirm their biocompatibility using human gingival fibroblasts and gingival keratinocytes [ 47 ] and in vivo allergy tests [ 48 ]. Since TEGDMA has a risk of disruption of vital cell functions, the cytotoxicity due to the unpolymerized monomers will be examined further [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the filler-loaded PMMA-based resin is considered suitable for use in dental applications, such as temporary crowns, provisional restorations, and denture bases. However, there is scope for further assessment of the cytotoxicity of PMMA-based reins to confirm their biocompatibility using human gingival fibroblasts and gingival keratinocytes [ 47 ] and in vivo allergy tests [ 48 ]. Since TEGDMA has a risk of disruption of vital cell functions, the cytotoxicity due to the unpolymerized monomers will be examined further [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current findings imply that the cytotoxicity of the PMMA-based resin may be acceptable for use in an oral environment. The biocompatibility of the PMMA-based resins will be further clarified using in vitro cytotoxicity using human gingival cells [47] and in vitro allergy tests [48] in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports indicate that, for the moment, the mixes of PMMA compatible with VPP 3D printing techniques are for dental technologies and implants [135][136][137], although a few studies have reported additional medical uses [138]. The notable characteristics of PMMAbased constructs include their good aesthetics, physicochemical properties, low cost, excellent biocompatibility, low toxicity, reliability, and good mechanical strength [130,132,133].…”
Section: Poly(methyl Methacrylate)mentioning
confidence: 99%
“…An innovative study using DLP-printed PMMA successfully built a tracheostomy tube which was later tested and functioned properly with no infections, allergies, or other reactions in rabbits [138]. It was reported that the PMMA-resin scaffold exhibited no fiber structures, contaminations, or surface cracks and also that cell viability was higher than in the control groups.…”
Section: Poly(methyl Methacrylate)mentioning
confidence: 99%
See 1 more Smart Citation